Formulasi Dan Evaluasi Sifat Fisik Pasta Ekstrak Binahong (Anredera cordifolia (Ten) Steenis) Dan Cangkang Telur Ayam Dengan CMC Na Sebagai Pengikat - Eryani, Mikhania Christiningtyas; Aditama , Agnis Pondineka Ria (Faculty of Pharmacy, University of Jember, 2024)
Binahong (Anredera cordifolia (Ten) Steenis) is a natural ingredient that can prevent tooth decay due to plaque. The purpose of this study was to formulate and evaluate the physical properties of binahong extract paste and chicken egg shells with various concentrations of CMC Na as a binder. The paste was formulated with various concentrations of CMC Na, namely 1.5% (F1), 2% (F2) and 2.5% (F3). The physical properties of the paste studied included organoleptic, homogeneity, pH, viscosity, spreadability and foam height. The results showed that variations in the concentration of CMC Na affected the organoleptic physical properties of color, viscosity and foam height of the paste. However, variations in the concentration of CMC Na had no effect on the pH and spreadability of the paste.